A study on student’s involvement in extracurricular activities towards student satisfaction: a case study among diploma students in UiTM Kedah / Annisa Ilyana Abd Razak ... [et al.] - Abd Razak, Annisa Ilyana; Ashaari, Awatif; Zakaria, Zalfaizah (2010)
The extracurricular is the one of activities that the student should involve at their school and university to brush up their skills in terms of soft skill to ensure all the student can compete in their future life. The purpose of this research is to know whether there is a relationship between student’s involvements in extra cocurricular activities toward student satisfaction in UITM Kedah. The objective of this research is to identify whether self interest, peers and extra curricular activities itself can create satisfaction to the student when joining extracurricular activities, and answering the research question of what is the type of extracurricular activities focusing to sport, art or academic that student in UiTM Kedah prefers. In this study, the researcher identified three factors that are self interest, peers and extra curricular activities itself. According to Johnson (2000) peers that influence the student are always a close person among the students. This research is conducted in UiTM Kedah and the population of this research is the entire Diploma student in UiTM Kedah. There have two types of sampling technique is used that is stratified random sampling and disproportionate stratified random sampling. The data is measured by using dichotomous scale, category scale and likert scale, where as questionnaires is developed with five parts of question to take specific information from the respondents.